Antecedents and Consequences of Female Consumer Expectations and Evaluations toward CSR Activities - Prima, Bery (UI Scholars Hub, 2021)
Many firms see Corporate Social Responsibility (CSR) as necessary investments in the community where the firms operate in order to ensure and safeguard sustainable operation for the future. This paper investigates the causal relationship between the antecedents and consequences of consumer expectations and evaluation to CSR activities. The original contribution of this study is that it focuses on the perceptions of female consumers on CSR activities of a multinational company.The research employed 175 women in the Greater Jakarta region as respondents, which consists of 92 housewives and 83 career women. Respondents are existing customer of a multinational consumer goods firm operating in Indonesia. Analysis was performed using the Structural Equation Modeling. Final model showed that customer’s evaluation on the firms’ financial and ethical statements positively influences expectations and evaluations, while Consumer evaluation of a firms’ CSR has indirect effect on Consumer’s Trust, Loyalty and Perceived Risk.